CRITERIA FOR ASSESSING THE EFFECTIVENESS OF PUBLIC GOVERNANCE IN INTERNATIONAL RATINGS AND INDICES (American Journal of Business Management, Economics and Banking, 2025)
This research analyzes the criteria for assessing the effectiveness of public governance in international ratings and indices. In particular, it examines global indicators such as the Worldwide Governance Indicators (WGI), Corruption Perceptions Index (CPI), and Global Competitiveness Index (GCI) to evaluate the efficiency of public institutions, anti-corruption efforts, political stability, rule of law, and economic competitiveness. The main goal of the study is to determine Uzbekistan’s position in international assessments, identify its strengths and weaknesses, and develop scientific and practical recommendations for improving the public administration system.